1996
DOI: 10.1093/mnras/282.3.1027
|View full text |Cite
|
Sign up to set email alerts
|

ROSAT HRI observations of the globular clusters M13 and M92

Abstract: We report on 40 kiloseconds of ROSAT HRI observations of the globular cluster M92 (NGC 6341) and 20 kiloseconds of observations of the globular cluster M13 (NGC 6205). We find that the low-luminosity (10 32.5 erg sec −1 at 7.5 kpc) source previously observed near the core of M92 with the ROSAT PSPC remains unresolved at HRI resolution; we can identify it with M92 with 99 per cent confidence. In M13 we find that the source seen with the ROSAT PSPC lies within the core and is possibly associated with the cluster… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…In 47 Tuc, of the candidate counterparts suggested by a variety of authors, Verbunt & Hasinger (1998) only retain three, on the basis of more accurate positions of the X-ray sources; these were also confirmed with Chandra. Ferraro et al (1997) suggested ultraviolet stars as counterparts for two sources found by Fox et al (1996) in NGC 6205 (see also ). An ultraviolet counterpart suggested by Ferraro et al (2000) for a source in NGC 6341 is incompatible with the position of that source (Geffert 1998).…”
Section: Some Information On the Luminous X-ray Sources In Globularmentioning
confidence: 81%
See 1 more Smart Citation
“…In 47 Tuc, of the candidate counterparts suggested by a variety of authors, Verbunt & Hasinger (1998) only retain three, on the basis of more accurate positions of the X-ray sources; these were also confirmed with Chandra. Ferraro et al (1997) suggested ultraviolet stars as counterparts for two sources found by Fox et al (1996) in NGC 6205 (see also ). An ultraviolet counterpart suggested by Ferraro et al (2000) for a source in NGC 6341 is incompatible with the position of that source (Geffert 1998).…”
Section: Some Information On the Luminous X-ray Sources In Globularmentioning
confidence: 81%
“…by Fox et al (1996) in NGC 6341 and NGC 6205. However, it is fair to say that the actual plethora of sources shown by the Chandra observations in virtually every cluster that it observed (Tables 8.2, 8.4) was unpredicted.…”
Section: Some Information On the Luminous X-ray Sources In Globularmentioning
confidence: 93%
“…ROSAT HRI and PSPC observations (Fox et al 1996;Verbunt 2001), revealed several dim X-ray sources in M 13. The HRI observations showed two core sources, whose unresolved PSPC spectrum could be fitted with a 0.9 keV thermal bremsstrahlung model (L 0.5−2.5 keV ∼ 2.5 × 10 32 ergs s −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Searching the SIMBAD database, none of the X-ray sources have an optical counterpart that lies within the error box of the X-ray determined coordinates. We have therefore tried to evaluate whether we see an overdensity of sources within the core of the cluster, in a similar manner to Fox et al (1996). We have used the log N -log S relation derived from XMM-Newton observations of the Lockman Hole (Hasinger et al 2001).…”
Section: Cluster Membershipmentioning
confidence: 99%